Phytosome-Enhanced Secondary Metabolites for Improved Anticancer Efficacy: Mechanisms and Bioavailability Review - Mardiana L; Milanda T; Hadisaputri YE; Chaerunisaa AY (Drug Design, Development and Therapy)
Lia Mardiana,1,2 Tiana Milanda,3 Yuni Elsa Hadisaputri,3 Anis Yohana Chaerunisaa4 1Doctoral Program, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 2Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari, Banjarmasin, 70123, Indonesia; 3Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 4Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, IndonesiaCorrespondence: Tiana Milanda; Yuni Elsa Hadisaputri, Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, Indonesia, Email tiana.milanda@unpad.ac.id; yuni.elsa@unpad.ac.idPurpose: Phytosome technology, an advanced lipid-based delivery system, offers a promising solution for enhancing the bioavailability and therapeutic efficacy of secondary metabolites, particularly in cancer treatment. These metabolites, such as flavonoids, terpenoids, and alkaloids, possess significant anticancer potential but are often limited by poor solubility and low absorption. This review aims to investigate how phytosome encapsulation improves the pharmacokinetic profiles and anticancer effectiveness of these bioactive compounds.Patients and Methods: This comprehensive review is based on an analysis of recent literature retrieved from PubMed, Scopus, and ScienceDirect databases. It focuses on findings from preclinical and in vitro studies that examine the pharmacokinetic enhancements provided by phytosome technology when applied to secondary metabolites.Results: Phytosome-encapsulated secondary metabolites exhibit significantly improved solubility, absorption, distribution, and cellular uptake compared to non-encapsulated forms. This enhanced bioavailability facilitates more effective inhibition of cancer pathways, including NF-κB and PI3K/AKT, leading to increased anticancer efficacy in preclinical models.Conclusion: Phytosome technology has demonstrated its potential to overcome bioavailability challenges, resulting in safer and more effective therapeutic options for cancer treatment. This review highlights the potential of phytosome-based formulations as a novel approach to anticancer therapy, supporting further development in preclinical, in vitro, and potential clinical applications. Keywords: phytosome, secondary metabolites, cancer, bioavailability